2019
DOI: 10.2147/cia.s158987
|View full text |Cite
|
Sign up to set email alerts
|

<p>Osmotic stress and mortality in elderly patients with kidney failure: a retrospective study</p>

Abstract: PurposeWater balance disorders are associated with a high risk of death in elderly patients. The role of osmotic stress intensity and its direction toward hypo- or hypernatremia is a matter of controversy regarding patients’ survival. The aims of this study were, first, to measure the frequency of cellular hydration disorders in patients over 75 years old hospitalized in nephrology department for reversible acute renal failure, and second, to compare the impact of hyperhydration and hypohydration on the risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The results of our analyses generally revealed an up-trending pattern of ORs for all outcomes in higher [Na] and older age groups. In accordance with other studies(11,12,32), our study demonstrated that the odds of inhospital mortality in all [Na] group increased with aging. This can be attributed to the fact that elderly patients with hypernatremia present fewer symptoms of hypernatremia compared to younger patients.…”
supporting
confidence: 93%
“…The results of our analyses generally revealed an up-trending pattern of ORs for all outcomes in higher [Na] and older age groups. In accordance with other studies(11,12,32), our study demonstrated that the odds of inhospital mortality in all [Na] group increased with aging. This can be attributed to the fact that elderly patients with hypernatremia present fewer symptoms of hypernatremia compared to younger patients.…”
supporting
confidence: 93%
“…Table 1 shows the incidence and prevalence of hyponatremia in the studies of the general population, CKD not on dialysis, hemodialysis, and peritoneal dialysis ( 10 , 27 54 ). Table 2 shows the incidence and prevalence of hypernatremia in the same population segments ( 10 , 28 30 , 32 36 , 38 40 , 47 , 53 55 ). The values for prevalence and incidence related to dysnatremias vary widely in each of the four categories of patients in Tables 1 , 2 and overlap substantially among the four patient categories.…”
Section: Reviewmentioning
confidence: 99%
“…Hypernatremia increases the risk for mortality in the general population ( 82 ) and in patients with CKD not on dialysis ( 10 , 34 36 , 38 ). In hemodialysis patients, hypernatremia was observed to be a risk factor for all-cause mortality ( 44 ) and mortality risk for causes other than cardiovascular disease or malignancy in a second study ( 46 ).…”
Section: Reviewmentioning
confidence: 99%